A sustainable integrated agroforestry system - Comolli, Luis R.; Schegg, Esteban; Infuleski, Cristian; Fassola, Hugo; von Wallis, Alejandra; Bulfe, Nardia M.; Barth, Sara R.; Gonzalez, Paola A.; Gauchat, María Elena; Munareto, Néstor; Gross, Victoria; Cruz, Paula; et al. (Frontiers in Plant Science, 2025)
IntroductionAgricultural intensification has boosted global food supply but has also driven deforestation, soil degradation, biodiversity loss, and greenhouse gas emissions, posing critical sustainability challenges. In response, alternative practices such as agroforestry have emerged, yet few long-term experimental systems exist that integrate high biodiversity with commercial perennial crops. Over 25 years, we have developed and refined a perennial, multi-species agroforestry system in northeastern Argentina, integrating Ilex paraguariensis (yerba mate) and 19 associated tree species.MethodsThe experimental design monitored crop yields, soil restoration metrics (including soil organic matter content), and population dynamics of the detrimental psyllid Gyropsylla spegazziniana. Long-term field data were collected from replicated agroforestry and monoculture plots to evaluate the ecological and agronomic performance of the system.ResultsThis biodiverse, perennial system restores degraded soils through sustained increases in organic matter, stabilizes or enhances I. paraguariensis yields relative to monoculture controls, substantially diminishes psyllid infestation through natural regulation, and facilitates broader biodiversity recovery, including avian and mammal recolonization. A striking and unplanned finding was the system’s resilience during the extreme 2021–2022 South American drought, heatwaves, and wildfires—plants within the agroforestry system showed markedly less stress than those in monocultures, underscoring its adaptive capacity.Discussion/ConclusionThese findings demonstrate the ecological and agronomic advantages of agroforestry as a scalable alternative to monoculture. By mimicking natural forests, our system shows how biodiversity-driven complexity enhances resilience, reduces dependence on external inputs, and provides climate adaptation and mitigation benefits. Integrated agroforestry offers a vital pathway to achieve the 2030 biodiversity targets of the CBD COP-15 and aligns agriculture with the UN Decade on Ecosystem Restoration.